Dispositivo de apoyo en los procesos de implementación y seguimiento de la ISO 9001 en las empresas de construcción. Actividad de enchape de piso en vivienda multifamiliar (2021)
This research work covers the subject of white work in construction through 3 specific pillars such as: labor (physical and mental effort that is used to carry out a job), performance (amount of work of some activity completely executed by a crew), waste (construction waste) and seeks to provide a solution to the different problems that throughout history have been repeated in the construction sector and that in the end have an effect on the project's economy (Budget); All this through the use of a file that allows specifically monitoring and controlling the fl ooring activity, which was identified through surveys carried out with different professionals, which is where there is an increase in the percentage of waste, lower yields, and in some cases unskilled labor.